The Perceptions of Critical Thinking and Inclusive Practice among Primary School Teachers - Afib Rulyansah (Universitas Pahlawan Tuanku Tambusai, 2023)
Curricula where inclusiveness towards all students is a priority, the most useful ability to tackle problems in the twenty-first century. This research aims to present primary school education applied by primary school teachers for the teaching and evaluation of critical and inclusive thinking. Using a qualitative method, the authors looked for candidates who have a real commitment to improving the profession of primary school teachers in the elementary school age range (about 7-12 years). Then, the author conducted in-depth interviews in September and October 2022 with ten elementary school teachers, of which 5 were from public schools and 5 were from private schools in Surabaya, Indonesia. Research shows that primary school teachers will recognize the need to develop students' critical thinking skills but are not adequately equipped to meet this demand. Elementary school teachers choose deliberation and cross-group interaction as key methods for developing critical thinking. These primary school teachers link the relationship between critical thinking and fair and high-quality schools. Critical thinking is very important if want to change society in a way that can assess reason, values, pluralism, and diversity.